Pengaruh Lifestyle, Fitur, Brand Image, Dan Kepercayaan Konsumen Terhadap Keputusan Membeli Smartphone Xiaomi Di Kota Surakarta - Miftahun Nurzanah; Aditya Liliyan (Universitas 45 Surabaya, 2023)
The purpose of the study is to ascertain the relationship between Lifestyle, Features, Brand Image, and Consumer Trust on Xiaomi smartphone purchase decisions in Surakarta City, as well as the impact of each factor on those decisions, respondents 97 make up the research sample as well. Utilizing the SPSS software, a quantitative research methodology was used. The study's findings show that the Lifestyle variable significantly influences people's decisions to buy Xiaomi smartphones in Surakarta City. In Surakarta City, feature variables significantly influence consumers' decisions to buy Xiaomi smartphones. The company's image in Surakarta City, and Xiaomi Smartphone Purchase Decisions. Between the consumer trust variables, the consumer trust variable has a considerable impact on smartphone purchase decisions in Surakarta City. In Surakarta City, the factors